Hypotonic Stress Induces RANKL via Transient Receptor Potential Melastatin 3 (TRPM3) and Vaniloid 4 (TRPV4) in Human PDL Cells. (March 2015) - Son, G.Y.; Yang, Y.M.; Park, W.S.; Chang, I.; Shin, D.M.
Bone remodeling occurs in response to various types of mechanical stress. The periodontal ligament (PDL) plays an important role in mechanical stress–mediated alveolar bone remodeling. However, the underlying mechanism at the cellular level has not been extensively studied. In this study, we investigated the effect of shear stress on the expression of bone remodeling factors, including receptor activator of nuclear factor–kappa B (NF-κB) ligand (RANKL) and osteoprotegerin (OPG), as well as its upstream signaling pathway in primary human PDL cells. We applied hypotonic stress to reproduce shear stress to PDL cells. Hypotonic stress induced the messenger RNA (mRNA) and protein expression of RANKL but not OPG. It also increased intracellular Ca 2+ concentration ([Ca 2+ ]i ). Extracellular Ca 2+ depletion and nonspecific plasma membrane Ca 2+ channel blockers completely inhibited the increase in both [Ca 2+ ]i and RANKL mRNA expression. We identified the expression and activation of transient receptor potential melastatin 3 (TRPM3) and vaniloid 4 (TRPV4) channels in PDL cells. Pregnenolone sulfate (PS) and 4α-phorbol 12, 13-didecanoate (4α-PDD), which are agonists of TRPM3 and TRPV4, augmented Ca 2+ influx and RANKL mRNA expression. Both pharmacological (2-aminoethoxydiphenyl borate [2-APB], ruthenium red [RR], ononetin [Ono], and HC 067047 [HC]) and genetic (small interfering RNA [siRNA]) inhibitors of TRPM3 and TRPV4 reduced the hypotonic stress–mediated increase in [Ca 2+ ]i and RANKL mRNA expression. Our study shows that hypotonic stress induced RANKL mRNA expression via TRPM3- and TRPV4-mediated extracellular Ca 2+ influx and RANKL expression. This signaling pathway in PDL cells may play a critical role in mechanical stress–mediated alveolar bone remodeling.